Partially-specified large games - Ehud Kalai (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2005)
The sensitivity of Nash equilibrium to strategic and informational details presents a diØ culty in applying it to games which are not fully specified. Structurally-robust Nash equilibria are less sensitive to such details. More-over, they arrise naturally in important classes of games that have many semi-anonymous players.
Keywords: 330; Spieltheorie; Nash-Gleichgewicht; Theorie